Acinetobacter Species: Phenotypic Characterization And Antimicrobial Resistance - Shrestha, Medhabi; Khanal, Basuda (Journal of Nobel Medical College, 2013)
Background: Acinetobacter species is ubiquitous, aerobic gram-negative coccobacilli that are now emerging as an important nosocomial pathogen. Objectives: The present study was designed to know the prevalence of Acinetobacter in various clinical samples, their characterization and their antibiotic susceptibility pattern in B.P. Koirala Institute of Health and Sciences, Dharan. Methodology: Hundred Acinetobacter isolates obtained from different clinical specimens were taken. Identification to species level was done according to standard microbiological methods. Antimicrobial susceptibility to 10 antimicrobial agents was performed by Kirby Bauer method with special reference to Minimum inhibitory concentration to meropenem. Result : The predominant Acinetobacter isolate was Acinetobacter calcoaceticus (42%) followed by Acinetobacter baumannii (34%) , Acinetobacter lwoffii (18%) and Acinetobacter junii (6%). Resistance pattern to various drugs were Meropenem (19%), Piperacillin (96%), Piperacillintazobactum (43%) , Amikacin (51%), Ceftazidime (84%), Ceftriaxone (66%), Co-trimoxazole (58%), Gentamicin (57%), Ciprofloxacin (55%), Tetracycline (53%) . Eleven isolates of Acinetobacter were resistant to Meropenem as detected by MIC testing whereas resistant Acinetobacter by disc diffusion technique were 19 in number. Conclusion: Occurrence of Acinetobacter in our hospital as an important clinical isolate is a serious matter of concern. Moreover, its involvement in wide spectrum of diseases and development of resistance to commonly used antimicrobials has further worsened the situation. Prudent use of antimicrobials, effective surveillance of antimicrobial resistance and adherence to infection control practices, perhaps are the key factors that may prevent the development and dissemination of resistance among the local isolates. Journal of Nobel Medical College Vol. 2, No.1 Issue 3 Nov.-April 2013 Page 43-48 DOI: http://dx.doi.org/10.3126/jonmc.v2i1.7675